Indicators for monitoring maternal and neonatal quality care: a systematic review - Pedro J. Saturno-Hernández; Ismael Martínez-Nicolás; Estephania Moreno-Zegbe; María Fernández-Elorriaga; Ofelia Poblano-Verástegui (BMC, 2019)
Abstract Background Research and different organizations have proposed indicators to monitor the quality of maternal and child healthcare, such indicators are used for different purposes. Objective To perform a systematic review of indicators for the central phases of the maternal and child healthcare continuum of care (pregnancy, childbirth, newborn care and postpartum). Method A search conducted using international repositories, national and international indicator sets, scientific articles published between 2012 and 2016, and grey literature. The eligibility criteria was documents in Spanish or English with indicators to monitor aspects of the continuum of care phases of interest. The identified indicators were characterized as follows: formula, justification, evidence level, pilot study, indicator type, phase of the continuum, intended organizational level of application, level of care, and income level of the countries. Selection was based on the characteristics associated with scientific soundness (formula, evidence level, and reliability). Results We identified 1791 indicators. Three hundred forty-six were duplicated, which resulted in 1445 indicators for analysis. Only 6.7% indicators exhibited all requirements for scientific soundness. The distribution by the classifying variables is clearly uneven, with a predominance of indicators for childbirth, hospital care and facility level. Conclusions There is a broad choice of indicators for maternal and child healthcare. However, most indicators lack demonstrated scientific soundness and refer to particular continuum phases and levels within the healthcare system. Additional efforts are needed to identify good indicators for a comprehensive maternal and child healthcare monitoring system.